Neoliberal and Transformation of the University of Botswana: From Public Education to Entrepreneurism - Marobela, M. N. (Archives of Business Research, 2024)
This article examines the concept of entrepreneurial university and its applicability to Botswana. This is a general conceptual analysis with a special focus directed at the University of Botswana. It traces its emergence and the extent to which it is embraced as an alternative to traditional model of education under the rubric of state-owned public university. Although entrepreneurial educational model is increasingly, getting global attention, it is not so widely established in the global south, where the role of the public sector in providing social services is still imperative. Understandably so because many people in developing countries are still struggling with the basics hence privately paid education whose raison-detre is profit making will not be affordable unless funded or subsidised by the state. The research provides insights into the influx of newly established privately owned universities which could be classified as entrepreneurial. Researchers contend that their emergence is driven by the neoliberal agenda in education which underpins the market supremacy and private universities as contributing to investment and job creation. These universities are not directly funded by the state, they are autonomous and self-run; the government only sponsors the students enrolled in their courses by paying their tuition fees.